Architect Vladimir Lojanica - Milašinović Marić, Dijana (Arhitektura i urbanizam, 2023)
Gallery of the Faculty of Fine Arts, June 2023. Exhibition on the occasion of the Grand Prize in Architecture, awarded by the Association of Architects of Serbia for lifetime achievement.
Keywords: Exhibition; Vladimir Lojanica; Grand Prize